Enhancing the Luminescence Efficiency of Triphenylamine-Thiophene Aggregation-Induced Emission Luminogens Using Shell-Isolated Nanoparticle-Enhanced Fluorescence (SHINEF) (2024)
Shell-isolated nanoparticle-enhanced fluorescence (SHINEF) is a variation of surface-enhanced fluorescence (SEF) that involves the use of core-shell nanostructures to enhance fluorescence signals. This increase in signals is achieved due to the enhanced local electric field produced by light stimulation toward the plasmonic metal core of the core-shell nanostructure. In SHINEF, a thin insulating shell is introduced around a plasmonic metal core, creating a structure that enhances the fluorescence of nearby molecules while minimizing the unwanted interactions with the metal core, such as energy transfer events. In this study, we explore the fluorescence enhancement produced by silver nanoparticles (AgNPs) coated with SiO2 for two triphenylamine-thiophene aggregation-induced emission (AIE) luminogens, 5-(4-(bis(4-methoxyphenyl)amino)phenyl)thiophene-2-carbaldehyde (TTY) and 5′-(4-(bis(4-methoxyphenyl)amino)phenyl)-[2,2′-bithiophene]-5-carbaldehyde (TTO), deposited on glass substrates. The results derived from emission and extinction spectra reveal that enhancement depends mainly on the concentrations of both molecules and AgNPs on the substrate as well as the selected excitation wavelength to carry out the measurement. A maximum experimental enhancement factor of 8.0 is achieved when the molecular concentration is at its lowest level, in combination with a higher AgNP concentration. These results are also rationalized in terms of computational simulation based on Mie theory. Simulated optical extinction spectra and the enhanced local external electric field around AgNPs have been carried out to compare with the obtained experimental results. This enhancement induces a significant decrease in lifetimes when the molecules are in the proximity of the nanostructured surface. These findings underscore the potential use of plasmonic nanoparticles as an effective alternative for enhancing the fluorescence of molecules with AIE characteristics.